The Influence of the Habit of Reading Asmaul Husana on the Formation of Religious Character of Grade VIII Students at Smpn 6 West Karawang - Laelatul Nur Hudiah; Iwan Hermawan; Nur Aini Farida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Humans are the most special creatures that God created. One thing that differentiates humans from other creatures is that they can think and make decisions using their minds. The way a person acts can be learned through education and habituation. Education has a very important meaning for human life. Education is more directed at developing character, attitude, personality, morals, or more towards affect. Teaching character education is important for students to achieve their educational goals. This research aims to find out whether there is an influence of the habit of reading Asmaul Husna on the formation of the religious character of class VIII students at SMPN 6 West Karawang. The method used is ex-post facto, that is, the researcher does not provide treatment to the variables studied. The population was all students at SMPN 6 West Karawang, totaling 1,308 students, while the sample in this study was taken from classes VIII D, VIII E, totaling 79 students. The data collection technique used is using questionnaires and documentation. As a result of the habit of reading Asmaul Husna for class VIII students at SMPN 6 West Karawang, there were 11 students (14%) in the low category, then there were 55 students (70%) in the medium category, and there were 13 students (16%) in the in the high category. So it can be understood that the habit of reading Asmaul Husna for class VIII students at SMPN 6 West Karawang is in the medium category. Forming the Religious Character of class VIII students at SMPN 6 West Karawang, there are 7 students (9%) in the low category, then there are 67 students (85%) in the serdang category, and there are 5 students (6%) in the low category. high, meaning that the formation of class VIII religious character at SMPN 6 West Karawang is in the medium category. From the results of the constants and coefficients of the simple linear regression equation, the regression equation is obtained Ý 15.619 + 0.526 The significance value is 0.05 (0.000 < 0.05), this means that H0 is rejected. Thus,